2005
DOI: 10.1016/j.molstruc.2005.04.043
|View full text |Cite
|
Sign up to set email alerts
|

An alternating chain of spider-like tris(peptides) stabilized by stacking and by N–H⋯N and N–H⋯OC hydrogen bonding

Abstract: The X-ray crystal structure of the novel spider-like trispeptide N,N 0 ,N 00 -tris(2-aminopyridine)benzene-1,3,5-tricarboxamide shows the unexpected formation of a new extended polymeric architecture. The structure is characterized by cooperative hydrogen bonding generating neighbouring pairs by self-assembly, and stacking between rings. Pairs of amide groups related by an inversion centre are connected into dimers via two N-H/O carbonyl and two N-H/N pyridyl intermolecular hydrogen bonds. The offset-stacked l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…At pH 10, it was observed that molecule 1 was involved in H-bonding leading to the formation of six-membered ring(s) and increases the conjugation. As a result of conjugation, increase in the π − π* transition was observed, which leads to the higher molar absorptivity (ε) ( Figure 1) [21][22][23][24][25][26][27]. A similar fact was applicable for molecule 2 and molecule 3 due to the formation of five-and four-membered chelation rings through H- bonding.…”
Section: Effect Of Ph Variation On Titled Moleculesmentioning
confidence: 78%
See 1 more Smart Citation
“…At pH 10, it was observed that molecule 1 was involved in H-bonding leading to the formation of six-membered ring(s) and increases the conjugation. As a result of conjugation, increase in the π − π* transition was observed, which leads to the higher molar absorptivity (ε) ( Figure 1) [21][22][23][24][25][26][27]. A similar fact was applicable for molecule 2 and molecule 3 due to the formation of five-and four-membered chelation rings through H- bonding.…”
Section: Effect Of Ph Variation On Titled Moleculesmentioning
confidence: 78%
“…The comparative FTIR analyses showed that the difference between the computational and experimental analysis was between 71-10 cm The major differences in the C9O and N-H frequencies of molecules 1 and 2 were observed, which was greater than 40 cm −1 . In addition to the above-mentioned fact (computational data in the gaseous phase and experimental in the solid/liquid phase), the other most effective reason behind it was the H-bonding [21][22][23][24]. H-bonding was not counted or optimized in computational analysis.…”
Section: Experimental Cum Computational Comparative Spectroscopic Anamentioning
confidence: 99%
“…Later, crystal structures of BTAs 4-14 (Scheme 4) were reported. 26,27,56,[64][65][66][67][68] The crystal structure of N,N 0 ,N 00 -tris(carboxymethyl)-1,3,5-benzenetricarboxamide trihydrate (4) was studied by Gong et al 26 The triacid molecule 4 crystallizes in a centrosymmetric space group and a three-dimensional H-bonding network is observed.…”
Section: Btas In the Solid State 31 Crystal Structure Analysis Of Btasmentioning
confidence: 99%
“…It has a remote H-bond donor group, in addition to the metal binding site, and so far it has only been used to coordinate Ru(II) ions [49] and more recently silver(I) ions [50]. In addition to coordination, also other weak forces, like hydrogen bonding and intermolecular non-covalent interactions should be taken into account [51][52][53][54][55]. In this respect Hnor appears to have a suitable structure to bind metal compounds, where coordination, H-bonding and π-π stacking may act in synergy.…”
Section: Introductionmentioning
confidence: 99%